Tecendo identidades nas fronteiras: o vestir em narrativas de mulheres bissexuais - Souza, Jamilie Santos de (2021)
This dissertation aims to investigate how the identity constructions of bisexual women take place through their dress and aesthetics, considering their existence in a hetero and mononormative society that privileges an essentialist view of human sexual identities and orientations. It intends to understand whether their corporal-aesthetic narratives, as gender technologies exposed to their concrete realities, perpetuate hegemonic norms or subvert binary statements, breaking established borders. Its theoretical basis are fashion studies, social psychology, feminist, queer and bisexual studies, and uses life life history’s narratives and core meanings as a methodology. Data collection for the survey was carried out from online conversation groups and individual online interviews with bisexual women participating in Bi-Sides’ virtual group. For individual online interviews, participants selected personal photographs. In the narratives of the participating bisexual women, dressing as a situated bodily act becomes a powerful tool for weaving identity to overcome opposing models that do not contemplate them. They can go to places not conceived by social constructions — the interstices of identities, a source of strength and creativity for movements for change